Strength Analysis of the MSBS-5.56B Rifle Handguard Assembly Loaded with an Under-Barrel Grenade Launcher - Michał GRĄZKA; Mirosław ZAHOR; Ryszard WOŹNIAK (Problemy Mechatroniki)
This paper presents the results of FEM (finite element method) numerical testing of the handguard of the MSBS-5.56B 5.56 mm calibre rifle complete with a 40 mm calibre under-barrel grenade launcher. The FEM calculations and the analysis of the calculations were intended to provide verification of the strength of the handguard subjected to the forces generated by the interaction with the grenade launcher during the launch of a grenade round. The results of the tests allowed the designers and process engineers to design the optimal shape of a handguard that will guarantee its safety during the operation of the rifle with the under-barrel grenade launcher.